El conflicto de Darfur: un reto para la credibilidad de la Unión Africana - Alaminos Hervás, María Ángeles (UNISCI Discussion Papers, 2008)
In the case of the Darfur crisis, the African Union expected to achieve its first success on the international level in the pacification of an African conflict; the Darfur conflict has been a challenge to its credibility. The African Union mission in Sudan (AMIS) tried to stop the crisis, but their limited economic and human resources were unable to do so. The protection of 3,500,000 people in situation of risk in Darfur has been a challenge to the AU and a test for the effectivity of its AMIS mission. The African Union wants to prove its importance as an organization, its potential for developing concrete actions, its preponderance as an actor in Africa and its relevance as an international actor.